METHODS OF DEVELOPING LANGUAGE IN A FOREIGN LANGUAGE VIA THE INTERNET - Mansurova, Shohista (Журнал иностранных языков и лингвистики, 2023)
Our article will consider ways of optimally using Internet resources in foreign language teaching. Their regular use in foreign language classes increases cognitive activity and general interest in learning of pupils and students, expands the scope of the educational process, makes it more interesting, effective and acceptable.